Altered metal distribution in the sr45‐1 Arabidopsis mutant causes developmental defects. (17th April 2022) - Fanara, Steven; Schloesser, Marie; Hanikenne, Marc; Motte, Patrick
SUMMARY: The plant serine/arginine‐rich (SR) splicing factor SR45 plays important roles in several biological processes, such as splicing, DNA methylation, innate immunity, glucose regulation, and abscisic acid signaling. A homozygous Arabidopsis sr45‐1 null mutant is viable, but exhibits diverse phenotypic alterations, including delayed root development, late flowering, shorter siliques with fewer seeds, narrower leaves and petals, and unusual numbers of floral organs. Here, we report that the sr45‐1 mutant presents an unexpected constitutive iron deficiency phenotype characterized by altered metal distribution in the plant. RNA‐Sequencing highlighted severe perturbations in metal homeostasis, the phenylpropanoid pathway, oxidative stress responses, and reproductive development. Ionomic quantification and histochemical staining revealed strong iron accumulation in the sr45‐1 root tissues accompanied by iron starvation in aerial parts. Mis‐splicing of several key iron homeostasis genes, including BTS, bHLH104, PYE, FRD3, and ZIF1, was observed in sr45‐1 roots. We showed that some sr45‐1 developmental abnormalities can be complemented by exogenous iron supply. Our findings provide new insight into the molecular mechanisms governing the phenotypes of the sr45‐1 mutant. Significance Statement: This study shows that some of the sr45‐1 mutant phenotypes result from a severe alteration in metal mobilization, localization and transport and that the exogenous application of iron can rescue the reproductive defects of the mutant. Our data fine‐tune our understanding of the physiological responses impaired in the mutant, such as the oxidative stress response, metal homeostasis, and the phenylpropanoid pathway.